Improving geometric thinking skills through learning cycles assisted by interactive geometry books - Fatihah, Jihan Jamilatul; Sudirman, Sudirman; Mellawaty, Mellawaty (Nashir Al-Kutub Indonesia, 2023)
This research aims to analyze the increase in geometric thinking skills after using the Learning Cycle assisted by an interactive Geometry Book. The research design used is an experiment Design. In addition, the participants in this research were students in class VIII B at a private school in Indramayu Regency. Apart from that, the test instrument in this research is a test sheet in the form of a description. Next, the data obtained from the pre-test and post-test were analyzed statistically using the paired samples t-test. Based on the research results, it shows that the N-gain score shows an average value of 0.8903 or 89.03%, which is included in the high category. Furthermore, based on the normality test of the pre-test and post-test data, it shows that both data are normally distributed. Apart from that, based on the results of the paired samples test calculation, the Sig value is known. (2-tailed), namely 0.000 < 0.05, then Ho is rejected and Ha is accepted. Therefore, this study concludes that there is a difference in the average increase in students' geometric thinking abilities before and after using the interactive learning cycle assisted by interactive geometry books.